The content of manufacturing strategy: a case study in colombian industries (2014)
Manufacturing strategy (MS) is a long-term plan for production and operations system aimed to support the company’s corporate strategy. The content of MS addresses the goals and strategic decisions to face competition. Despite the number of contributions on this subject, few studies have been conducted in the Colombian context. Therefore, this article shows the results of a study undertaken in 36 Colombian companies addressing the three main components of the MS content: competitive priorities, strategic decision areas and the management’s approach to manufacturing. The results allow two groups of companies with different performance level to be identified, as well as the relationship of this performance with strategic decision areas and the management’s approach to manufacturing.